Design and validation of a questionnaire to identify the social representations on climate change of teachers from Normal colleges in Mexico - Bello Benavides, Laura Odila (IE Revista de Investigación Educativa de la REDIECH, 2021)
This paper explains the process used in the design and validation of a demoscopic instrument which purpose was to know the social representations (SR) and educational practices on climate change (CC) in a group of academics from Normal colleges: trainers of faculty. Considering that the training of teachers in climate change education (CCE) is a central task in the incorporation of CC in the curricula of both basic education and that of Normal schools, in the first stage, the activities focused on the operationalization of the SR theory for the object of study: CC, recognizing its biophysical, political-economic, and social dimension, along with global and regional impacts. The demoscopic instrument was based on the analytical category system, and it was validated with an expert test with six specialists on the subject. In the second phase, the reliability tests, the instrument was piloted and assessed using Cronbach’s Alpha statistic, with a result of 0.874. It had 59 items, and it was applied in five Normal colleges in the state of Veracruz, Mexico.